2013
DOI: 10.1371/journal.pone.0070247
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Patterns Trigger Differential Neural Signature of Emotional Processing in Adolescents

Abstract: BackgroundResearch suggests that individuals with different attachment patterns process social information differently, especially in terms of facial emotion recognition. However, few studies have explored social information processes in adolescents. This study examined the behavioral and ERP correlates of emotional processing in adolescents with different attachment orientations (insecure attachment group and secure attachment group; IAG and SAG, respectively). This study also explored the association of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 69 publications
(134 reference statements)
2
22
0
1
Order By: Relevance
“…Based on previous studies of moral evaluations and empathic responses, we expected to observe major activity in the vmPFC, dlPFC, pSTS, amygdala, and insula for the intentionally-harmed-persons condition811. Based on a prior study60, we expected higher activity in the vmPFC, dlPFC, and amygdala for CG than DG, and higher activity in the right pSTS/TPJ for DG than CG. We expected these effects to occur in two different time windows: an early time window between 150 and 300 ms after stimulus onset, and a late time window between 600 and 800 ms after stimulus onset.…”
Section: Methodsmentioning
confidence: 92%
“…Based on previous studies of moral evaluations and empathic responses, we expected to observe major activity in the vmPFC, dlPFC, pSTS, amygdala, and insula for the intentionally-harmed-persons condition811. Based on a prior study60, we expected higher activity in the vmPFC, dlPFC, and amygdala for CG than DG, and higher activity in the right pSTS/TPJ for DG than CG. We expected these effects to occur in two different time windows: an early time window between 150 and 300 ms after stimulus onset, and a late time window between 600 and 800 ms after stimulus onset.…”
Section: Methodsmentioning
confidence: 92%
“…For example, analyzing ERP responses to infant emotional faces studies using narrative measures of attachment found neural correlates associated with attentional processing (i.e., N200, P3) to be less prominent in insecure mothers (Fraedrich et al, 2010; Leyh et al, 2016a). Accordingly, studies using self-report measures of attachment found decreased ERP amplitudes in response to emotional faces in avoidant subjects (Zhang et al, 2008), as well as a response bias in favor of positive stimuli (Chavis and Kisley, 2012), while others found insecurely attached individuals to be less able to accurately discriminate between different facial emotion expressions on a neurophysiological level (Escobar et al, 2013; for a review also see Gander and Buchheim, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Face response ERPs were segmented to stimulus onset, beginning 200‐ms prestimulus and continuous for 1 000 ms after. Segments were filtered in EEGlab using a 0.3 to 30 Hz zero‐phase shift FIR bandpass filter, a filtering range selected based on its use in prior emotional face‐processing studies . The Automatic Artefact Removal toolbox was used to remove ocular and electromyographic artefacts via spatial filtering and blind source separation.…”
Section: Methodsmentioning
confidence: 99%
“…Segments were filtered in EEGlab 69 using a 0.3 to 30 Hz zero-phase shift FIR bandpass filter, a filtering range selected based on its use in prior emotional face-processing studies. [70][71][72] The Automatic Artefact Removal toolbox 73 was used to remove ocular and electromyographic artefacts via spatial filtering and blind source separation. Bad channels were identified and interpolated using the ERP PCA Toolkit.…”
Section: Event-related Potential Analysismentioning
confidence: 99%